2023
DOI: 10.1097/phh.0000000000001715
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Culture-Negative Pulmonary Tuberculosis—Alameda County, 2010-2019

Abstract: Context: Patients with culture-negative pulmonary TB (PTB) can face delays in diagnosis that worsen outcomes and lead to ongoing transmission. An understanding of current trends and characteristics of culture-negative PTB can support earlier detection and access to care. Objective: Describe epidemiology of culture-negative PTB. Design, Setting, Participants: We utilized Alameda County TB surveillance data from 2010 to 2019. Culture-negative PTB cases met clinical but not laboratory criteria for PTB per US Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…Figure 2 and Figure 3 reveal pre-and post-treatment chest images of two patients with culture-positive and culture-negative subclinical pulmonary TB. culture-positive ones, reflecting less extensive tissue damage [15,16]. However, the present study revealed a few such lesions exclusively in the culture-negative group, though not statistically significant due to their rarity.…”
Section: Resultscontrasting
confidence: 71%
See 3 more Smart Citations
“…Figure 2 and Figure 3 reveal pre-and post-treatment chest images of two patients with culture-positive and culture-negative subclinical pulmonary TB. culture-positive ones, reflecting less extensive tissue damage [15,16]. However, the present study revealed a few such lesions exclusively in the culture-negative group, though not statistically significant due to their rarity.…”
Section: Resultscontrasting
confidence: 71%
“…This aligns with the statement that Mtb may be contained within granuloma in the early stage, resulting in minimal pathology and a lack of symptoms [ 8 ]. Interestingly, prior studies also found that individuals with culture-negative pulmonary TB had fewer cavitary lesions than culture-positive ones, reflecting less extensive tissue damage [ 15 , 16 ]. However, the present study revealed a few such lesions exclusively in the culture-negative group, though not statistically significant due to their rarity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations